2016
DOI: 10.1016/j.pcad.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence for Saturated Fat and for Sugar Related to Coronary Heart Disease

Abstract: Dietary guidelines continue to recommend restricting intake of saturated fats. This recommendation follows largely from the observation that saturated fats can raise levels of total serum cholesterol (TC), thereby putatively increasing the risk of atherosclerotic coronary heart disease (CHD). However, TC is only modestly associated with CHD, and more important than the total level of cholesterol in the blood may be the number and size of low-density lipoprotein (LDL) particles that contain it. As for saturated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
143
1
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(171 citation statements)
references
References 138 publications
4
143
1
7
Order By: Relevance
“…Meta-analyses of observational studies and available clinical trials have not been able to find any reliable link between saturated fat and CVDs [1][2][3][4][5][6][7] which has been the pillar of official nutritional guidelines for more than three decades. A decrease of CVD prevalence/mortality occurs only when saturated fat is replaced by polyunsaturated fat (PUFAs) which is more likely to be related to the beneficial effects of PUFAs on blood lipid profiles, rather than to any harmful role of saturated fat.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analyses of observational studies and available clinical trials have not been able to find any reliable link between saturated fat and CVDs [1][2][3][4][5][6][7] which has been the pillar of official nutritional guidelines for more than three decades. A decrease of CVD prevalence/mortality occurs only when saturated fat is replaced by polyunsaturated fat (PUFAs) which is more likely to be related to the beneficial effects of PUFAs on blood lipid profiles, rather than to any harmful role of saturated fat.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, even this conclusion was recently questioned and attributed to methodological flaws [8]. On the other hand, we are witnessing growing evidence of the fundamental role of carbohydrates and high glycaemic index/load in the aetiology of CVDs [1][2][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…sucrose) produce greater degrees of metabolic abnormalities than does glucose (either isolated as a monomer, or in chains as starch) and may present greater risk of CHD. To reduce the burden of CHD, guidelines should focus particularly on reducing intake of concentrated sugars, specifically the fructose-containing sugars like sucrose and high-fructose corn syrup in the form of ultra-processed foods and beverages [19] Others have found that consumption of added sugar is associated with development and/or prevalence of fatty liver, dyslipidemia, insulin resistance, hyperuricemia, CVD and type 2 diabetes and failure to stimulate leptin production [20][21][22][23].…”
Section: High Sugar Intake Increases Risk For Cardiovascular Diseasementioning
confidence: 99%
“…[5] Taking in too much sugar would result to the storing of excess sugar as triglycerides and synthesis of cholesterol. [6] High concentrations of triglycerides raise the low-density lipoproteins (LDL) high-density lipoprotein (HDL), which causes the deposit of cholesterol to the arterial walls. This also lowers the HDL concentration, which counteracts the LDL.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Other effects of excess intake of sugar include obesity, diabetes, and heart diseases. [6] With these diseases becoming apparent, many sugar substitutes, such as sucralose, stevia, aspartame, sugar alcohols, and many more, have emerged. These substitutes claim to be better as these have lesser calories compared to regular sugar and that they neither increase nor decrease blood sugar levels significantly.…”
Section: Introductionmentioning
confidence: 99%